Approximation by quaternion (p,q) $(p,q)$-Bernstein polynomials and Voronovskaja type result on compact disk - Haifa Bin Jebreen; Mohammad Mursaleen; Ambreen Naaz (Advances in Difference Equations, 2018)
Abstract In this paper, we define the (p,q) $(p,q)$-Bernstein polynomials of degree m of a quaternion variable. We obtain some approximation results, and also the Voronovskaja type result with quantitative upper estimates is proved.